Customary Law or State Law: The Settlement of Marine Resource Disputes in The Kei Islands Community - Ratuanak, Andreas M.D.; Irianto, Sulistyowati; Lestrarini, Ratih (UI Scholars Hub, 2022)
The people of the Kei Islands have known cases settlement system since the olden days, namely the Customary judiciary, a forum in the Larvul Ngabal customary law system that holds a high authority, which is obeyed by the community and is often the main choice in resolving disputes. With a field study approach, this study aims to explain how the settlement process of natural resources disputes by a “customary judge” in the Kei Islands is still used as a reference by the community. What are the reasons? This study discovered that customary settlement forums are still used to resolve marine resource disputes and deemed to provide a sense of justice. Customary settlements are not only aimed at punishing the perpetrators, but also to restore the impact of the dispute on individual victims, their families and their social environment. This study also discovered that the customary settlements carried out in the Kei Islands have developed from the dated dichotomy and tend to produce hybrid settlement models.